Do what you want : the book that shows you how to create a career you'll love - Bate, Nicholas (Pearson, 2012)
This book explains the seven steps that can help you manage, control and maintain a career that will help fulfil your goals and ambitions. Whether you are unemployed and planning your next move, a graduate planning your future or an employee planning your escape, this smart book is packed with practical, life-changing advice that is simple and straightforward to apply. The vital guidance will help you understand and adapt to the realities of the job market today and develop a focussed and realistic career plan for a secure future.